SENSE OF RELATING TO A COMMUNITY IN 19th CENTURY ISTANBUL: Foreign Schools and Their Sustainable Architectural Preservation - Onur, Selen Yazici (YILDIZ TECHNICAL UNIV, 2011)
19th century Ottoman modernization period was such a circle that westernization concept had shown its results in form of place projections. The multicultural social structure of Ottoman Imperial has been affected by French Reforms and coeval beliefs in Europe; freedom, democracy, humanity ideas, especially after the rights goverment gave under the name of kaputilasyon, come into word in daily life. This renewal period, which can be defined as westernization movement and can be dated to Lale Devri, has shown its reflections in building actions generally as military education buildings. Foreign schools, even somes' history related to 16th - 17th century, has reached their education context at the same period. Since 19th century, foreign schools got changed; some changed their names, others consoludate with another under a new name and most of them closed by the end of century. Today, the number of foreign schools in Istanbul is 11. Those schools with their qualified and modern education programs, intelligence in discipline and different building structures which is a result of the additional extensions made since they opened, were demanded by Muslim families for wishing a better and modern education for their children. Those schools, both in social and physical structure differed from that times Ottoman educational institutions. Even today, with the additional relation of the country it belongs, they have developed the sense of belonging to a community. Those historical school buildings need to be preserved with all sort of values they own.
Keywords: Foreign country schools; Istanbul; modernization; foreigners; social and cultural structure; architectural preservation; sustainability; Engineering